Mucosal Defense Against Giardia at the Intestinal Epithelial Cell Interface - Solaymani-Mohammadi, Shahram (Frontiers in Immunology, 2022)
Human giardiasis, caused by the protozoan parasite Giardia duodenalis (syn. Giardia lamblia, Giardia intestinalis, Lamblia intestinalis), is one of the most-commonly identified parasitic diseases worldwide. Chronic G. duodenalis infections cause a malabsorption syndrome that may lead to failure to thrive and/or stunted growth, especially in children in developing countries. Understanding the parasite/epithelial cell crosstalk at the mucosal surfaces of the small intestine during human giardiasis may provide novel insights into the mechanisms underlying the parasite-induced immunopathology and epithelial tissue damage, leading to malnutrition. Efforts to identify new targets for intervening in the development of intestinal immunopathology and the progression to malnutrition are critical. Translating these findings into a clinical setting will require analysis of these pathways in cells and tissues from humans and clinical trials could be devised to determine whether interfering with unwanted mucosal immune responses developed during human giardiasis provide better therapeutic benefits and clinical outcomes for G. duodenalis infections in humans.